Fluensulfone: A New “Tool in the Tool Box” to Manage Plant-parasitic Nematodes in Vegetable Production - Gilma X. Castillo; Monica Ozores-Hampton; Pablo A. Navia Gine (EDIS, 2018)
Plant-parasitic nematodes pose a problem in agricultural systems by feeding on crops, therefore affecting their yield. Fluensulfone is a chemical that can be applied using various methods to manage the impact of plant-parasitic nematodes on crop production. This 6-page document discusses the characteristics and use of fluensulfone as a tool for nematode management practices. Written by Gilma X. Castillo, Monica Ozores-Hampton, and Pablo A. Navia Gine and published by the UF/IFAS Department of Horticultural Sciences, January 2018. http://edis.ifas.ufl.edu/hs1313